Whole-Genome Sequencing of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli From Human Infections in Finland Revealed Isolates Belonging to Internationally Successful ST131-C1-M27 Subclade but Distinct From Non-human Sources - Kurittu, Paula; Khakipoor, Banafsheh; Jalava, Jari; Karhukorpi, Jari; Heikinheimo, Annamari (Frontiers in Microbiology, 2022)
Antimicrobial resistance is a growing concern in public health, particularly for the clinically relevant extended-spectrum beta-lactamase (ESBL) and AmpC-producing Enterobacteriaceae. Studies describing ESBL-producing Escherichia coli clinical samples from Finland to the genomic level and investigation of possible zoonotic transmission routes are scarce. This study characterizes ESBL-producing E. coli from clinical samples in Finland using whole genome sequencing (WGS). Comparison is made between animal, food, and environmental sources in Finland to gain insight into potential zoonotic transmission routes and to recognize successful AMR genes, bacterial sequence types (STs), and plasmids. ESBL-producing E. coli isolates (n=30) obtained from the Eastern Finland healthcare district between 2018–2020 underwent WGS and were compared to sequences from non-human and healthy human sources (n=67) isolated in Finland between 2012–2018. A majority of the clinical isolates belonged to ST131(n=21; 70%), of which 19 represented O25:H4 and fimH30 allele, and two O16:H5 and fimH41 allele. Multidrug resistance was common, and the most common bla gene identified was blaCTX-M-27 (n=14; 47%) followed by blaCTX-M-15 (n=10; 33%). blaCTX-M-27 was identified in 13 out of 21 isolates representing ST131, with 12 isolates belonging to a recently discovered international E. coli ST131 C1-M27 subclade. Isolates were found to be genetically distinct from non-human sources with core genome multilocus sequence typing based analysis. Most isolates (n=26; 87%) possessed multiple replicons, with IncF family plasmids appearing in 27 (90%) and IncI1 in five (17%) isolates. IncF[F1:A2:B20] replicon was identified in 11, and IncF [F-:A2:B20] in four isolates. The results indicate the ST131-C1-M27 clade gaining prevalence in Europe and provide further evidence of the concerning spread of this globally successful pathogenic clonal group. This study is the first to describe ESBL-producing E. coli in human infections with WGS in Finland and provides important information on global level of the spread of ESBL-producing E. coli belonging to the C1-M27 subclade. The results will help guide public health actions and guide future research.